Serum F.D.P. Measurement as a Screening Test for Thrombo-Embolic Disease - Vasilescu, C.; Jones, D. R. B.; Webber, Anne; Webber, R. G.; Allan, N. C.; Ruckley, C. V. (Thrombosis and Haemostasis, 1975)
Serum F.D.P. values are elevated in venous thrombo-embolic disease. In order to define the place of daily serum F.D.P. estimation as a screening test 300 consecutive patients admitted to medical wards and 70 undergoing operation have been studied. All patients were screened for venous thrombosis (D.V.T.) with the 125I-fibrinogen test and if positive they were further investigated by lung scanning and phlebography. All had daily blood sampling for F.D.P. and fibrinogen. F.D.P. were estimated by the Staphylococcal Clumping test to provide rapid results, backed up by the Tanned Red Cell Haemag-glutination Inhibition Immunoassay (Wellcome). The mean F.D.P. in medical patients with no detectable thrombo-embolic disease was 10.5 ug/ml. In patients with positive leg scans the mean was 43.3 ug/ml. In surgical patients with negative leg scans the mean F.D.P. was 15.4 ug/ml and with positive leg scans 38.9 ug/ml. In those with positive lung scans it was 275 ug/ml.We conclude that a finding of elevated serum F.D.P. in hospital patients strongly favours the diagnosis of venous thrombo-embolic disease. Low F.D.P. values do not exclude the condition.